COMPORTAMENTO DO CONSUMIDOR DE PRODUTOS TECNOLÓGICOS: ANÁLISE DOS UNIVERSITÁRIOS DE GUARAPUAVA - PR - PAPI, PEDRO PAULO (2016)
This study aims to measure the propensity to technology of university students from the Higher Education Institutions - HEI - of the city of Guarapuava - PR, using the search tool Technology Readiness Index - TRI 2.0. The instrument analyzes from a different perspective consumers of technology products, noting conductive variables to action as optimism and innovativeness; and inhibiting the consumption variables such as discomfort and insecurity. In addition to the TRI 2.0, the research made use of the Economic Classification Criterion Brazil - ECCB to classify individuals surveyed according to economic classes and measure the purchasing power of the university students. The instruments were used following the quantitative approach with survey research, which collected data from a sample of 372 university students from all county HEI. From the sample it was possible to classify respondents in: pioneers (13%), operators (12%), hesitant (13%), skeptics (42%) and laggards (20%), rating proposed by TRI 2.0 describing the behavior of consumers in relation to technological product offerings. Another result achieved was the categorization of respondents in economic classes, following the criteria of the ECCB, demonstrating that the purchasing power of the population tested is above the national average for the same age group, which is a positive point for the inclusion of technology products to this population. The results obtained through statistical analysis showed a positive trend relationship between the average income of individuals with propensity index of technology products consumer and defined as group most likely to consume young people with an average age of 21; male; members of the B2 class, with an average monthly income of R $ 4,427.36.